2015
DOI: 10.1039/c4pp00320a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a “push—pull” structure on the turn-on fluorescence of photochromic thio-ketone type diarylethenes

Abstract: a series of diarylethene compounds with a thiophene bridging unit have been synthesized to investigate the relationship between molecular structure and photochromic properties. In particular, the fluorescence properties related to compound 1 were investigated. The results showed that a six-membered ring carrying an electron-donating sulfur atom and an electron-withdrawing carbonyl group is necessary to form a "push-pull" system for the fluorescence of 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In turn, the possibility to switch fluorescence with optical inputs offers the opportunity to overcome the limitations that diffraction imposes on the spatial resolution of conventional fluorescence images. As a result, mechanisms for the optical control of fluorescence with photochromic compounds can ultimately evolve into invaluable operating principles for the visualization of biological specimens with unprecedented resolution. Indeed, representative examples of photochromic probes with optimal properties for subdiffraction imaging have been designed already, relying on diarylethenes, imidazole dimers, rhodamines, and spiropyrans. We developed a family of fast and stable photochromic compounds based on the photoinduced opening and thermal closing of an oxazine ring. We demonstrated that their reversible interconversion can be exploited to control the efficiency of electron- and energy-transfer processes and switch the emission of fluorescent partners. , Additionally, the structural changes associated with the photoinduced opening of the oxazine ring can be engineered to control reversibly the electronic structure of a covalently connected fluorophore. These transformations alter the ability of the latter to absorb exciting photons and emit as a result. In fact, our mechanism for fluorescence photoactivation can be replicated at the single-molecule (SM) level to allow the stochastic reconstruction of images with spatial resolution at the nanoscale. ,, …”
Section: Introductionmentioning
confidence: 99%
“…In turn, the possibility to switch fluorescence with optical inputs offers the opportunity to overcome the limitations that diffraction imposes on the spatial resolution of conventional fluorescence images. As a result, mechanisms for the optical control of fluorescence with photochromic compounds can ultimately evolve into invaluable operating principles for the visualization of biological specimens with unprecedented resolution. Indeed, representative examples of photochromic probes with optimal properties for subdiffraction imaging have been designed already, relying on diarylethenes, imidazole dimers, rhodamines, and spiropyrans. We developed a family of fast and stable photochromic compounds based on the photoinduced opening and thermal closing of an oxazine ring. We demonstrated that their reversible interconversion can be exploited to control the efficiency of electron- and energy-transfer processes and switch the emission of fluorescent partners. , Additionally, the structural changes associated with the photoinduced opening of the oxazine ring can be engineered to control reversibly the electronic structure of a covalently connected fluorophore. These transformations alter the ability of the latter to absorb exciting photons and emit as a result. In fact, our mechanism for fluorescence photoactivation can be replicated at the single-molecule (SM) level to allow the stochastic reconstruction of images with spatial resolution at the nanoscale. ,, …”
Section: Introductionmentioning
confidence: 99%
“…[15] The fluorescenceoft he compound was thought to be due to the bridge unit containing the six-membered ring with sulfur and carbonyl groups forming a" push-pull" system. [16] Thus, to improve the photochromic properties, and especially the fluorescenceo fd iarylethene 1,aseries of derivatives, 2-7,r etaining the "push-pull system" was synthesized,a nd their photophysical properties were studied. Interestingly,d uring our study with 1-7,w eunexpectedly found that the diarylethenes had electrochromic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported a novel “turn‐on” fluorescent diarylethene—2,3‐bis(2‐methylbenzo[ b ]thiophen‐3‐yl)‐5,6‐dihydro‐4 H ‐thieno[2,3‐ b ]thiopyran‐4‐one ( 1 )—and its successful application to live cell imaging (Scheme ). [15] The fluorescence of the compound was thought to be due to the bridge unit containing the six‐membered ring with sulfur and carbonyl groups forming a “push–pull” system 16. Thus, to improve the photochromic properties, and especially the fluorescence of diarylethene 1 , a series of derivatives, 2 – 7 , retaining the “push–pull system” was synthesized, and their photophysical properties were studied.…”
Section: Introductionmentioning
confidence: 99%